Mosques as Knowledge Development Centers: Youth Involvement and Perceptions in Kuching, Sarawak - Adibah, Yusuf; Khairul Aidil Azlin, Abd Rahman; Wan Noor Faaizah, Wan Omar; Nadzirah, Yusuf; Farah, Zaini; Nangkula, Utaberta; Adam Andani, Mohammed (EAI, 2021)
The purpose of this study is to ascertain youth perspectives, measures, and involvement in activities related to the mosque as a centre for knowledge growth among youth specifically in Kuching, Sarawak. A quite number of youth are not participating the Islamic activities held by the mosques as the mosque only main focus is to attract the elderly. In the structure of global governance, the mosque is the first and most important Muslim foundation. Initially, Prophet Muhammad (PBUH) established this base as a location for developing and spreading Islam, a rock-solid building that no other location on the planet can match for immaculateness, holiness, or attractiveness. In today's society, the vast majority of visitors to mosques are senior citizens. The youth don't seem to want to join or visit mosques. The major goal of this article is to examine the elements and reasons why the youths do not attend mosque institutions. This article discusses the current situation of Malaysian youth and mosques. Through this research paper, people will learn and understand that youth participation is critical to the society's development of a strong Ummah.